Optimization of Mechanical Properties and Manufacturing Time through Experimental and Statistical Analysis of Process Parameters in Selective Laser Sintering - Adrian Korycki; Christian Garnier; Valerie Nassiet; Charles Tarek Sultan; France Chabert (Advances in Materials Science and Engineering)
A statistical analysis of the response of the parameters has been led by a design of experiments to extract the most influential parameters in the selective laser sintering process. The parametric study was carried out by varying five parameters on the SLS machine and by looking at their influence on five groups of responses relating to the physical, mechanical, and thermal properties as well as to the printing duration. The mathematical models of the response surfaces were established by linking the responses to factors and their interactions. The model of regression uses not only the interaction between regressors but also nonlinear logical functions. These statistical models were used to define an optimal set of parameters. The geometry and density of specimens made of polyamide 12 confirm that increasing the distance between successive laser beam passes allows a significant manufacturing time reduction. The mechanical properties depend mostly on laser power and scan count. We conclude that a low laser power applied twice can improve the properties of the printed part. By optimizing the laser parameters, the targeted mechanical properties are obtained with over 33% of production time savings.